Perceptions of Collaboration between Virtual and Human Teachers in Online Education - Declercq, Lieselot; De Wever, Bram; Tuytens, Melissa (Proceedings of the International Conference on Networked Learning, 2024)
This study delves into the perceptions of teachers regarding the collaboration between virtual and human teachers in online education. It is situated within the broader context of artificial intelligence (AI) in education, with a particular focus on Generative Artificial Intelligence (Gen AI) and its potential to transform online learning. This study aims to explore the possibilities of Virtual Humans (VH) as humanized Gen AI entities. More specifically, in this presentation, we study the perceptions of online teachers of d-teach online school regarding VH. This study employs a survey that combines the Agent Persona Instrument (API-R) and the Technology Acceptance Model (TAM) to measure the participants' perceptions with respect to using a VH as a digital co-teacher. The primary research objective is thus to understand how these stakeholders perceive VH roles and effectiveness in supporting the learning process. Follow up interviews are planned to deepen our insights on how real teachers think about virtual humans as a teacher. Although specific results are pending at this stage, the study promises to provide valuable insights into teachers' perspectives. Beyond the confines of the school, this research has the potential to benefit global education and training by enhancing the quality, efficiency, accessibility, and inclusivity of online education.